2020
DOI: 10.1111/jvim.15985
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac heartworms in dogs: Clinical and echocardiographic characteristics in 72 cases (2010‐2019)

Abstract: Background: Heartworms, a cause of pulmonary hypertension (PH) in dogs, can migrate from the pulmonary arteries into the heart resulting in life-threatening caval syndrome (CS). Objectives: To describe clinical and echocardiographic characteristics in dogs with intracardiac heartworms including estimated heartworm burden and frequency of PH and pigmenturia. Animals: Seventy-two client-owned dogs with heartworms. Methods: Retrospective study. Data collected from an electronic medical records search for dogs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 41 publications
(167 reference statements)
3
28
1
1
Order By: Relevance
“…Forty-six of these mosquitoes were found in Burgenland. In none of these 205 mosquitoes has DNA of D. immitis been found to date but several dogs in a local shelter, all originating from Hungary, tested positive for D. immitis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Forty-six of these mosquitoes were found in Burgenland. In none of these 205 mosquitoes has DNA of D. immitis been found to date but several dogs in a local shelter, all originating from Hungary, tested positive for D. immitis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since scientists have proven significant pathogenicity of nematodes of the species Dirofilaria immitis Leidy, 1856, it is important to establish various criteria that determine the severity of the disease in animals, including hematological parameters (Donahoe et al, 1976;Maerz, 2020;Romano et al, 2021). Our research has shown that the severity of deviations from the hematological parameters of dogs with heartworm disease caused by parasitism of D. immitis depends on the level of microfilaremia.…”
Section: Discussionmentioning
confidence: 85%
“…This is due to the localization of these parasites in the right ventricle and pulmonary arteries. Severe disorders of all body systems, especially cardiovascular, can cause animal death (Hoch & Strickland, 2008;Maerz, 2020;Romano et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The dirofilariasis of dogs caused by the species Dirofilaria immitis (Nematoda, Onchocercidae) is the most pathogenic and widespread in the world. Its danger is confirmed by the high mortality of infected animals, poor results in their treatment and the specific cycle of parasite development, with the infection occuring through the bites of blood-sucking insects, the mosquitoes (González-Morteo, 2015;Silaghi et al, 2017;Romano et al, 2021). Thus, the diagnostics of dirofilariasis today remain a topical issue.…”
Section: Discussionmentioning
confidence: 99%
“…The most common and pathogenic of them is the species Dirofilaria immitis Leidy, 1856, due to the localization of these parasites in the right ventricle and pulmonary arteries. D. immitis causes severe disorders of all body systems, especially the cardiovascular one, and death (Hoch & Strickland, 2008;Maerz, 2020;Romano et al, 2021). The definitive hosts of helminths are more than 30 species of animals (dog, domestic and wild cat, fox, wolf, coyote, dingo, bear, panda, beaver, raccoon, ferret, coati, otter and a number of other mammals).…”
Section: Introductionmentioning
confidence: 99%